PENGARUH SISTEM AKUNTANSI KEUANGAN DESA, PEMANFAATAN TEKNOLOGI INFORMASI DAN PENGAWASAN TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA - Luh Putu Pratiwi Sintya Ningsih (UNHI Press, 2021)
Accountability is an obligation to be responsible for the success or failure in carrying out the mission of an organization in achieving a predetermined goal. This study aims to determine the effect of the village financial accounting system, the use of information technology and supervision on the accountability of village fund management in villages throughout Ubud District. The sample in this study was 95 village officials. The sampling method used was purposive sampling. The data analysis technique used in this research is descriptive statistics, validity test, reliability test, classical assumption test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression, coefficient of determination, model feasibility, t-test. From the results of this study, the village financial accounting system does not have a significant effect on the accountability of village fund management. The use of information technology has a positive and significant effect on the accountability of village fund management. Supervision has a positive and significant effect on the accountability of village fund management.